2015
DOI: 10.3102/0034654314566989
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and Pitfalls of Multimedia and Interactive Features in Technology-Enhanced Storybooks

Abstract: A meta-analysis was conducted on the effects of technology-enhanced stories for young children’s literacy development when compared to listening to stories in more traditional settings like storybook reading. A small but significant additional benefit of technology was found for story comprehension (g+ = 0.17) and expressive vocabulary (g+ = 0.20), based on data from 2,147 children in 43 studies. When investigating the different characteristics of technology-enhanced stories, multimedia features like animated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
248
1
18

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 320 publications
(298 citation statements)
references
References 89 publications
(134 reference statements)
13
248
1
18
Order By: Relevance
“…However, Mayer (2010) and Surjono (2015) advise that excessive use of multimedia may or may not lead to effective learning, and Takacs, Swart, and Bus (2015) postulated that visual information would distract learners' ISSN 2327-5499 2015 attention. The experimental study of Rummer, Schweppe, Fürstenberg, Scheiter, and Zindler (2011) further specified that complexity of multimedia information would increase mental effort and thus hinder the learning outcomes, but this finding was not in line with the present study's results.…”
Section: Discussion Implications and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Mayer (2010) and Surjono (2015) advise that excessive use of multimedia may or may not lead to effective learning, and Takacs, Swart, and Bus (2015) postulated that visual information would distract learners' ISSN 2327-5499 2015 attention. The experimental study of Rummer, Schweppe, Fürstenberg, Scheiter, and Zindler (2011) further specified that complexity of multimedia information would increase mental effort and thus hinder the learning outcomes, but this finding was not in line with the present study's results.…”
Section: Discussion Implications and Conclusionmentioning
confidence: 99%
“…Multimedia also has been considered as the prevalently tool used by teachers of hospitality program (Feinstein et al, 2005) because many previous studies indicated multimedia can provide learners with nonverbal information and thus is able to improve the comprehensibility of the contents being delivered (Salmon, 2014;Takacs, Swart, & Bus, 2015;Verhallen, Bus, & de Jong, 2006). However, it is to our knowledge that pertinent research about the possible advantages of adopting multimedia web-based technology in culinary skill training is scarce, particularly when Chinese culinary skills are at stake.…”
Section: Culinary Arts Training and Multimedia Web-based Technologymentioning
confidence: 99%
“…Recently, several studies (e.g. McKenney & Voogt, 2009;Takacs, Swart, & Bus, 2015;Van de Sande, Segers, & Verhoeven, in press) have shown that technology has potential to foster these early literacy strands, providing that the specific software applications meet certain features and that teachers know how to embed the technology in their classroom practice. This was an important reason to study if and how pre-service programmes are working to develop teacher TPACK in the domain of early literacy.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies exploring the impact of digital reading tools on children's emergent literacies claim that the use of multimedia features such as hotspots, game-like activities or scrawling in the book leads to shallow reading and short attention spans (e.g. Takacs, Swart & Bus, 2015). It is suggested that such features necessitate skills and abilities like task switching, which involve an excessive cognitive load that may have negative consequences for story comprehension (e.g.…”
Section: E-book Activities In Early Childhood Educationmentioning
confidence: 99%